THE EFFECT OF COMPANY SIZE, LEVERAGE, LIQUIDITY, AND INFLATION RATE ON EARNINGS GROWTH - Setiawan, Deni; Maulana, Yasir; Adzimatinur, Fauziyah (Universitas Kuningan, 2024)
This study aims to determine the Effect of Company Size, Leverage, Liquidity and Inflation Rate on Profit Growth Case Studies in Industrial Sector Companies both partially and simultaneously. The research methods used in this study are descriptive and verificative methods. This study uses secondary data in the form of company financial statements which are analyzed using penel data regression which includes classical assumption tests, model selection, coefficients of determination and hypothesis testing (F test and t test). The population in this study was 54 companies for 5 years. The samples in this study were taken using purposive sampling into 42 companies for 5 years and 210 data were observed. The results of this study show that (1) company size, leverage, liquidity and inflation rate simultaneously have a significant effect on profit growth, (2) company size has a positive and significant effect on profit growth, (3) leverage has a negative and significant effect on profit growth, (4) liquidity has a negative and insignificant effect on profit growth, (5) inflation rate has a negative and significant effect on profit growth.